Effect of Enriched Artemia sp. by EPA (Eicosapentaenoic Acid; C20:5n-3) and DHA (Docosahexaenoic Acid; C22:6n-3) on Survival Rate of Swimming Crab Portunus pelagicus - Suprayudi, M. Agus; Mursitorini, E.; Jusadi, D. (Jurnal Akuakultur Indonesia, 2006)
Nutrient content of natural food is one of the main factors for determining the successful of marine fish fry production.  EPA (Eicosapentaenoic Acid) and DHA (Docosahexaenoic Acid) are two essential fatty acids for marine fish larvae.   Low levels of EPA and DHA content in natural food is major problem in marine fish larval production.  Rotifers fed by Nannochloropsis contained EPA about 0.94%-1.46% and DHA was limited, while in Artemia was 0.27%-0.39% EPA and DHA was undetected (Suprayudi et al., 2002a).  Feeding on supplemented Artemia with EPA 28G and DHA 70G in ratio of 1:1 could not significantly improved its survival rate and larval development time, while growth by length and carapas width at first crab were higher  than  that of fed with unenriched Artemia. Keywords: EPA, DHA, Artemia, swimming crab, Portunus pelagicus   ABSTRAK Kandungan nutrisi dalam pakan alami merupakan salah satu faktor utama yang menentukan keberhasilan produksi benih spesies akuatik laut.  EPA (asam ekosapentanat) dan DHA (asam dokosaheksanat) merupakan 2 asam lemak esensil bagi larva ikan laut.  Kandungan EPA dan DHA yang rendah pada pakan alami merupakan masalah utama dalam produksi larva ikan laut.  Rotifer yang diberi pakan Nannochloropsis mengandung EPA 0,94%-1,46% dan DHA dengan jumlah yang sangat kecil, sementara Artemia EPA mengandung 0,27%-0,39% dan DHA tidak terdeteksi (Suprayudi et al., 2002a). Pemberian Artemia yang diperkaya dengan EPA 28G dan DHA 70G dengan perbandingan 1:1 tidak memberikan hasil yang signifikan pada tingkat kelangsungan hidup dan waktu perkembangan larva rajungan, sementara pertumbuhan panjang dan lebar karapas lebih baik pada crab 1 dibandingkan dengan yang diberi Artemia tidak diperkaya. Kata kunci: EPA, DHA, Artemia, rajungan, Portunus pelagicus